Sentinel apiaries – epidemiological surveillance – training programas as strategies for early detection of the SHB in AHB in Costa Rica - Calderón, Rafael A. Fallas (2023)
Ponencia presentar en el en el APIMONDIA : 48th Congreso Internacional de Apicultura ( 2023: setiembre 4-8 : Santiago, Chile)